ANALISIS CORPORATE GOVERNANCE PERCEPTION INDEX TERHADAP KEBIJAKAN DIVIDEN DI INDONESIA (Studi Empiris pada Perusahaan Peserta CGPI Tahun 2011-2016) - Yulina Masyrifatun Nisa’; Tarmizi Achmad (Diponegoro Journal of Accounting, 2018)
This study aims to examine the effect of Corporate Governance Perception Index (CGPI) as an independent variable to the dividend policy taken by the company as a dependent variable.The population in this study is the entire company that voluntarily registered itself as a participant of CGPI and certainly a company listed on the Indonesia Stock Exchange in 2011-2016. The method used in this study is purposive sampling with the following criteria: (1) public listed companies listed on the BEI, (2) companies participating in CGPI assessment and rating organized by IICG, (3) companies that publish their financial statements on the Indonesia Stock Exchange (BEI), (4) the company that distributes dividends to shareholders between 2011-2016. This research uses multiple regression analysis to test the research hypothesis.The results of this study indicate that Corporate Governance Perception Index (CGPI) has a significant positive effect on dividend policy and confirms the theory of outcome valid in Indonesia.